Human Resources for Care in Latin America and the Caribbean: Current Needs and Future Demands - Villalobos-Dintrans, P (Elsevier Inc., 2024)
Objectives: To estimate the current gap and the necessary supply of human resources for care (HRC) for older people experiencing severe care dependence in Latin America and the Caribbean (LAC). Design: Simulation study using previous estimations of severe care dependence for LAC countries. Setting and Participants: Older people (aged 65+) experiencing severe care dependence in 26 countries of LAC. Methods: We calculated the current gap and the necessary supply of HRC in 2020, 2035, and 2050 assuming a mix of complementary human resources, in line with regional standards for long-term care (LTC) schemes, and differing levels of care coverage. Results: Considering 100% coverage of LTC services for the population aged 65+ experiencing severe care dependence, the region will need almost 5 million people working full-time in the sector. This figure is expected to increase to more than 14 million by 2050. Nurse assistants and nurses will be the professional profiles in highest demand. In addition, the region requires 2 million rehabilitation professionals in 2020, and this figure will increase to more than 6 million in 2050. Conclusions and Implications: The rapid aging process in LAC will bring several challenges and opportunities to the region. Countries should start designing strategies to reduce the current gaps of HRC to meet older people s care needs in the coming years, in terms of both quantity and competencies, to help ensure that their human rights are met. © 2023 AMDA – The Society for Post-Acute and Long-Term Care Medicine